English-tagalog & tagalog-english dictionary - De Guzman, Maria Odulio (Mandaluyong City: Anvil Publishing, 2019)
This dictionary is a concise guide that shows you how to use English and Tagalog effectively. It contains instructions on grammar and balarila; each word is used in two or more sentences in English and Tagalog. It also has tips on functional grammar as well as language and reading; geographical names; translation of commonly used terms in school; and idiomatic expressions in English and Tagalog. Finally , it also offers a list of the most commonly mispronounced words.
Includes appendix.